Wave damping by seagrass meadows in combined wave‐current conditions. Issue 7 (25th May 2022) - Beth Schaefer, Rachel; Nepf, Heidi
Abstract: Laboratory experiments using an artificial seagrass meadow modeled after Zostera marina measured the impact of following currents on meadow‐induced wave decay as a function of the imposed current velocity U c, wave velocity U w, and wave Cauchy number C a w, which is the ratio of hydrodynamic drag force to restoring force due to blade stiffness. For small wave‐induced reconfiguration of individual seagrass blades C a w < 2000 and U c / U w > 0.5, the addition of current enhanced reconfiguration, which decreased wave decay relative to pure wave conditions. In contrast, when the wave‐induced reconfiguration was large C a w > 2000, the addition of following current did not significantly enhance blade reconfiguration or impact wave damping. Due to canopy drag, the current velocity within the submerged meadow, U 1, was significantly smaller than the depth‐averaged current U c, and a better prediction of wave decay was achieved using U 1 as the relevant velocity. The measured wave decay validated predictions based on a modified Cauchy number, defined for combined waves and current and using the in‐canopy velocity U 1 . Practical assumptions to facilitate the prediction of wave decay in the field are discussed and validated.